Legal Analysis of Post-Divorce Child Protection Rights (Case Study: Decision No. 3/Pdt.G/2025/PTA.Smd) - Situngkir, Devani Elisabeth; Nurbaiti, Nurbaiti (Journal of Law and Economics, 2025)
Rising divorce rates have triggered custody disputes where children's fundamental rights face systematic neglect, generating psychological trauma and legal ambiguity. This research examines post-divorce child protection under Law No. 35 of 2014 on Child Protection, analyzing Decision No. 3/Pdt.G/2025/PTA.Smd as a case study. Two primary questions guide the investigation: first, how courts operationalize the child welfare principle in custody determinations within Decision No. 3/Pdt.G/2025/PTA.Smd; second, how Law No. 35 of 2014 safeguards children's rights amid post-divorce custody conflicts. Employing normative juridical methodology through statutory, conceptual, and case study approaches, the research reveals that Law No. 35 of 2014 establishes child welfare as the paramount consideration in all child-related decisions. The principle addresses physical, psychological, social, and spiritual dimensions to secure optimal development. Decision No. 3/Pdt.G/2025/PTA.Smd demonstrates practical application: the judicial panel awarded custody to the biological mother based on her superior capacity to provide appropriate care environments while preserving paternal visitation rights. The ruling simultaneously mandates financial support obligations, reinforcing continued parental accountability post-divorce. The decision effectively operationalizes child-centered legal frameworks through balanced consideration of caregiving capacity, emotional bonding, and economic responsibility.